Graph theory to evaluate communication in industrial multiagent systems. (18th July 2011) - Ben Hmida, Faten; Lejouad Chaari, Wided; Tagina, Moncef
Industrial systems are complex, distributed and need high-quality tools for their control and monitoring. Although, multiagent systems (MAS) are well adapted to such applications, there is still a gap between academic research on MAS and their potential use on a large scale as in industry. Such domain, with important economic stakes, requires high-performance and reliable applications. However, performance issues were rarely discussed in multiagent environments; the existing works focus only on evaluation of multiagent design methodologies and development platforms. In this paper, we identify, among the MAS features, those that make them suitable to industrial applications. Then, we give an overview on MAS evaluation and we propose a measurement model based on the graph theory to analyse several communication facets in MAS. An experimentation is carried out on two architectures of a multiagent diagnosis application. The comparison of the results points out the correlation between the measurement model and the communication network.